The Use of Teams Games Tournament (TGT) in Teaching Reading Narrative Text at Eleventh Grade Students at MA. Nurul Huda Sedati - Muhammad Ulil Aydiy (P-SEMART JOURNAL, 2021)
This research is focused on the use of Team Games Tournament (TGT) in learning to read Narrative text in eleventh grade. This research was conducted using qualitative descriptive methods. Eleventh grade science at MA Nurul Huda is the subject of this study. The data in this study were checklist data, student questionnaires, and videos of the TGT learning process. All activities during reading learning using the TGT method are the source of data in this study. The results showed that learning to read narrative texts using the Teams Games Tournament (TGT) learning method can be done in eleventh grade. In addition, student responses to the use of the TGT method in learning to read narrative texts have many positive impacts for students, reinforced by the results of the questionnaire which showed 83% of students gave positive responses and 13% of students gave negative responses. The researcher gave some suggestions to 1) the English teacher to improvise the TGT learning model such as group discussions, 2) students to apply their understanding in the learning process.